Knowledge, attitudes and practices about contraception amongst schoolgirls aged 12-14 years in two schools in King Sabata Dalindyebo Municipality, Eastern Cape - Pamela Mda; Don O'Mahony; Parimalarani Yogeswaran; Graham Wright (AOSIS, 2013)
Background: In South Africa the teenage fertility rate is high. About 42% of women have their sexual debut by 18 years of age and 5% by 15. These young women are also at risk of sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) infection. Despite widespread availability of contraception, 18% of sexually active teenagers do not use any. Previous research on the knowledge of, attitudes to and practices of contraception by teenagers has focused on older adolescents. Objectives: This study explored knowledge, attitudes and practices about contraception amongst 12-14 year old unmarried schoolgirls with a view to inform planning of programmes to assist in reducing teenage pregnancies. Methods: A qualitative study design with purposive sampling was used to select participants from two government-run schools in King Sabata Dalindyebo Municipality. In-depth and focus group interviews were conducted after obtaining written consent from parents and assent from participants. Interviews were audiotaped, transcribed verbatim, translated and analysed thematically. Findings: Participants reported that young adolescents were sexually active, which included high risk sexual behaviour such as multiple partners and casual and transactional sex. Knowledge about contraceptives varied widely. Condoms were the most preferred method of contraception, but it is unknown whether they ever used condoms as they professed to talk about the behaviour of others rather than themselves. Injectable contraceptives were believed to have long-term negative effects. Common sources of contraceptive information were friends or peers, school curriculum and to a lesser extent family members. Conclusions: Findings of the study suggest that young adolescents are sexually active and have inadequate knowledge and misconceptions about contraception. These findings should inform educational programmes about risks of early sexual activity and about contraception.